Brucella genomics: macro and micro evolution - Guzman-Verri, Caterina (2020)
Se seleccionó la licencia Creative Commons para este envío. El documento trae lo siguiente: © 2020 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/). (En caso de duda consultar a Meilyn Garro).